2017
DOI: 10.3389/fimmu.2017.01452
|View full text |Cite
|
Sign up to set email alerts
|

The Vagus Nerve in the Neuro-Immune Axis: Implications in the Pathology of the Gastrointestinal Tract

Abstract: The vagus nerve (VN) is the longest nerve of the organism and a major component of the parasympathetic nervous system which constitutes the autonomic nervous system (ANS), with the sympathetic nervous system. There is classically an equilibrium between the sympathetic and parasympathetic nervous systems which is responsible for the maintenance of homeostasis. An imbalance of the ANS is observed in various pathologic conditions. The VN, a mixed nerve with 4/5 afferent and 1/5 efferent fibers, is a key component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
210
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(233 citation statements)
references
References 179 publications
(196 reference statements)
2
210
0
8
Order By: Relevance
“…These results concur with previous studies showing that vagal stimulation can attenuate TNF production in arthritis (Bassi et al, 2017; Koopman et al, 2016), ischemia/reperfusion (Altavilla et al, 2006; Bernik et al, 2002; Cai et al, 2009), hemorrhage/resuscitation (Cai et al, 2009; de Souza et al, 2010), post-operative recovery (Grech et al, 2016), pancreatitis (Van Westerloo et al, 2006), endotoxemia (Borovikova et al, 2000; Deitch and Ulloa, 2010; Huston et al, 2006b) and severe sepsis (Ulloa, 2011; van Westerloo et al, 2005; Wang et al, 2004). Our results also concur with previous studies showing that exercise increased the vagal cardiovascular tone (Bonaz et al, 2017; Carnevali and Sgoifo, 2014; Ulloa et al, 1998). But, other study reported that exercise modulates cardiovascular but not through the vagus nerve (Neto et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results concur with previous studies showing that vagal stimulation can attenuate TNF production in arthritis (Bassi et al, 2017; Koopman et al, 2016), ischemia/reperfusion (Altavilla et al, 2006; Bernik et al, 2002; Cai et al, 2009), hemorrhage/resuscitation (Cai et al, 2009; de Souza et al, 2010), post-operative recovery (Grech et al, 2016), pancreatitis (Van Westerloo et al, 2006), endotoxemia (Borovikova et al, 2000; Deitch and Ulloa, 2010; Huston et al, 2006b) and severe sepsis (Ulloa, 2011; van Westerloo et al, 2005; Wang et al, 2004). Our results also concur with previous studies showing that exercise increased the vagal cardiovascular tone (Bonaz et al, 2017; Carnevali and Sgoifo, 2014; Ulloa et al, 1998). But, other study reported that exercise modulates cardiovascular but not through the vagus nerve (Neto et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…4b). Given that exercise can increase the vagal tone (Bonaz et al, 2017; Carnevali and Sgoifo, 2014) and that the vagus nerve can inhibit splenic TNF production (Borovikova et al, 2000; Huston et al, 2006a; Huston et al, 2006b), we analyzed whether the vagus nerve contributes to the effects of exercise. Unilateral right cervical vagotomy did not prevent the anti-inflammatory potential of exercise (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota interacts with BAs in the enterohepatic circulation by converting primary to secondary BAs which, in turn, regulate microbiota by exerting antimicrobial effects. 189 This scenario might also involve a neurohormonal mechanism with vagal-mediated gallbladder emptying before exercise. 185 Regular physical activity also leads to increased vagal tone 186,187 and decreased expression of inflammatory markers, 187 although recent studies provide conflicting results or suggest reduction in circulatory apoptosis marker 112,188 , an effect correlating with high cardiorespiratory fitness.…”
Section: Inflammationmentioning
confidence: 99%
“…Unlike healthy controls, patients with IBS appear to be conscious of these sensory inputs, which is interpreted as abdominal discomfort or pain. The vagus nerve has been linked to activation of the hypothalamic‐pituitary stress axis, and modification of gut‐originating pain signaling, which, in turn, leads to altered gut function . The entire GI tract in rats is innervated by the vagus, and the dorsal motor nucleus of the vagus and vagal afferents are sensitive to GLP‐1 .…”
Section: Introductionmentioning
confidence: 99%